2, 3‐Dichloro‐5, 6‐Dicyano‐1, 4‐Benzoquinone (DDQ)‐Mediated Tandem Oxidative Coupling/Intramolecular Annulation/Dehydro‐Aromatization for the Synthesis of Polysubstituted and Fused Pyridines. Issue 21 (19th September 2019) - Cheng, Dongping; Deng, Zhiteng; Yan, Xianhang; Wang, Mingliang; Xu, Xiaoliang; Yan, Jizhong
Abstract: A DDQ‐mediated tandem reaction of 1, 3‐diarylpropenes and β‐enaminoesters/4‐aminocoumarins is disclosed. It involves oxidative coupling, intramolecular annulation and dehydro‐aromatization reaction, which provides an efficient and mild method for the synthesis of polysubstituted and fused pyridines under metal‐free conditions. Abstract :